Characterization and prediction of B-cell epitopes - Liang, Zhao (2013)
A B-cell epitope is a set of antigen surface residues which can be recognized by an antibody. Identifying epitopes facilitates the understanding of the basic recognition mechanism of immune responses, which in turn guides disease diagnosis, vaccine design and drug development. However, the identification of epitopes is challenging due to the complicated nature of antigen-antibody interactions as well as the context-awareness principle behind the interaction. Context-awareness highlights the existence of multiple epitopes in antigens and the reconfiguration of epitope residues when an antigen interacts with a different antibody. A coarse binary classification of antigen regions into epitopes or non-epitopes without specifying antibodies may not accurately reflect this biological reality. To accurately and rationally detect the epitopes of an antigen, comprehensive analysis of multiple epitopes is carried out. This is followed by antibody-specific epitope prediction in line with the principle of context-awareness and antibody-agnostic epitope prediction which is capable of predicting one or multiple epitopes that are consistent with the rule of